Behavior Of Society In Management PNM Mekaar Loan Capital - Affandi, Ismi; Harahap, Raja Putra Sakti; Basri, Tengku Hasan (Al-Hijrah: Journal of Islamic Economics And Banking, 2024)
This article aims to determine community behavior in providing loan capital from PNM Mekaar (Civil National Capital to foster a prosperous family economy) to the community in Tanjung Jati Village PTPN II District. Binjai, Langkat Regency. The government has established a financing program for business capital for people who lack capital. One of them is PT. PNM (Civil National Capital). PT. PNM (Civil National Capital) was established as part of the government's strategic solution to improve the welfare and economic equality of society through developing access to capital and capacity building programs for Micro, Small and Medium Enterprises (MSMEs). This research uses qualitative research methods, using primary data sources. The results of the research are community behavior in managing loan capital from PNM Mekaar (Civil National Capital to foster a prosperous family economy) in the community in Tanjung Jati Village PTPN II Kec. Binjai, Langkat Regency with its development Business Enhancement Income Which Done by poor people by taking advantage of it Source Available Power.